Single-grain two-fragment method for dating terrace deposits using red thermoluminescence from quartz - Ganzawa, Y.; Azuma, T. (Ancient TL, 2009)
We undertook red thermoluminescence (RTL) dating of terrace deposits in northern Japan using an improved method that requires the analysis of only a single quartz grain. In previous studies, two components (the apparent equivalent dose (Ap-De) and the residual level dose (Rl-De) after exposure to artificial light) were evaluated from separate multiple-grain aliquots to obtain the age of deposits by RTL and other luminescence techniques. We developed a new method, called the “single-grain two-fragment” (SGTF) method, to determine the values of Ap-De and Rl-De. In this method, two fragments are prepared by breaking a single quartz grain using a hammer and nail. The use of recently developed, highly sensitive RTL measurement apparatus enabled the successful detection of RTL signals from single quartz grains (300–500 μm in diameter) with doses as low as 20 Gy. The performance of the SGTF method was assessed by a case study involving the analysis of two samples of terrace deposits. Two separate RTL age groupings (241±20 and 113±17 ka) were determined as minimum equivalent doses (De), as deduced from Ap-De and Rl-De using the single aliquot regeneration (SAR) method. These ages are in good agreement with estimates of the age of the terraces based on geological criteria (OIS 5e and OIS 7).